ANALISIS PERBANDINGAN PERHITUNGAN VOLUME METODE BIM DAN METODE KONVENSIONAL (STUDI KASUS: GEDUNG BANK MANDIRI PALEMBANG) - Lulu Isnaini Ija; Nauval Rabbani; Dwi Kumalasari; Annas Firman; Muhammad Abdul Malik Annasir (Rang Teknik Journal, 2026)
The advancement of digital technology has encouraged the construction industry to improve efficiency, accuracy, and cost control through the implementation of Building Information Modeling (BIM). This study compares concrete volume calculations using the conventional two-dimensional method and the BIM-based approach with Autodesk Revit. The case study focuses on the construction of the Bank Mandiri Building in Palembang, a 12-storey reinforced concrete structure consisting of bored piles, pilecaps, columns, beams, and slabs. The conventional method involved identifying structural dimensions from AutoCAD drawings and calculating volumes using Microsoft Excel based on geometric formulas, while the BIM method was conducted by developing a three-dimensional structural model in Revit and extracting quantities through the schedule/quantities feature. The comparison was analysed by calculating the percentage difference between both methods. The results show that the overall difference in concrete volume is 0.1599%, indicating a relatively small deviation. The average differences for bored piles and pilecaps are minimal, while columns, beams, and slabs show slightly higher variations, with beams and slabs presenting the largest discrepancies. These differences are mainly influenced by modelling details, drawing interpretation, rounding processes, and potential human error in both approaches. Overall, the findings demonstrate that BIM provides accurate and efficient quantity estimation; however, its reliability depends on the modeller’s precision. Therefore, both conventional and BIM methods remain complementary and can be used together to enhance accuracy and minimise errors in concrete volume estimation.  Keywords: Quantity-Takeoff, BIM, Concrete